Factors Causing Moral Degradation Of Teenagers: A Study On Adolescent Promiscuity - Fadilah, Nurul; Diru, Achmad Errie; Rizky, Muhammad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Promiscuity is a common social phenomenon in adolescent life. Various factors cause this phenomenon, inseparable from the aspects of psychology and sociology that are less considered so that it affects the growth and development of adolescents. In this study using survey research that will be used to collect data from respondents and interviews. The data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. Based on the survey data that has been conducted, there are a total of 26 respondents who filled out a survey containing questions about the frequency of community visits, the frequency of finding promiscuity activities, examples of promiscuity activities found, responses, and community criticism of the phenomenon of promiscuity at the Baitul Izzah Mosque. The conclusion of the research is that unhealthy associations are born in adolescents who are separated from supervision and control by parents. Although it sounds good in the view of general terminology, dating in the Islamic perspective is a form of zina, as explained by several statements and verses in the Qur'anic sural about the prohibition of relationships before marriage between men and women who are not muhrim. In fact, the phenomenon of dating among teenagers today is no longer a taboo subject to be discussed and acted upon, but has become a commonplace in our society.